The emerging framework of financial regulation - Goodhart, C. A. E.; London School of Economics and Political Science (London : Central Banking Publications, 1998)
This contains some general analytical studies of the regulatory process; the implications of derivatives for regulations and the comments of a number of eminent guests at our seminars and conferences; eg. lawyers regulators and practitioners on regulatory issues and the final sections concerns how European developments are influencing regulation both in the UK, and elsewhere.
On cover: A collection of papers compiled by the Financial Markets Group of the London School of Economics.
Includes bibliographies.
aia 2/09/16
Loans
Keywords: Financial services industry; Financial services industry -Law Legislation; Financial services industry-State supervision; Banking law; Banks and banking